Evaluation of Pork-Specific DNA Primers for Halal Authentication in Processed Meats - Salsabila, Aisyah Izmi Hamida; Wahyudi, Didik (Halal Science, 2025)
Ensuring the authenticity of halal-labeled food products is a growing global concern, particularly due to recurring reports of adulteration with non-permissible components such as pork. Molecular techniques, especially polymerase chain reaction (PCR), offer a sensitive and specific means to detect pork DNA in processed meats, where traditional protein-based assays often fail due to denaturation. This study evaluates the sensitivity of five pork-specific mitochondrial DNA primers, ND5, Cytochrome B(1), Cytochrome B(2), PPA8, and Pork (F2/R1), for detecting Sus scrofa DNA in processed meat products using conventional PCR. Genomic DNA was extracted from corned pork and beef meatball samples and amplified using each primer under optimized conditions. Of the five primers tested, only PPA8, Pork (F2/R1), and Cytochrome B(2) produced clear, specific amplicons in pork samples, with no cross-reactivity observed in beef samples. PPA8 and Pork (F2/R1) demonstrated the strongest and most consistent amplification, suggesting superior sensitivity and reliability. ND5 and Cytochrome B(1) showed poor performance, indicating limited applicability in processed food matrices. These findings confirm the utility of selected primers in halal authentication and highlight the importance of empirical validation in primer selection. Future work should focus on expanding primer testing across diverse processed food types and incorporating quantitative PCR to establish detection thresholds.